ESTUDIO PRELIMINAR DE LA VARIABILIDAD INTRAESPECÍFICA DE PROTEÍNAS SEMINALES EN Araujia hortorum FOURN (Apocynaceae). - Gonzales Medrano y Cols., M.F (2019)
Araujia hortorum Fourn is a sudamerican perennial climbing plant that performs like an invasive in crops and natural reserve areas. There have been controversies about to consider it as independent specie or like an intraspecific entity dependent to A. sericifera Brot. (Araujia sericifera f. hortorum Malme). As a complement approach to define its situation, It has been compared some seeds samples coming from nine populations from Argentina‟s pampean region (A. cf. hortorum) and another from Misionera jungle (A. cf. sericifera). through use the method of polyacrylamide gel electrophoresis (PAGE-SDS) and immnunoblot assay (IT, “immunoblotting”), it have been able to detect the presence of 19 and 18 protein bands respectively, although they are not coincident to each other. The use of the Jaccard Index shows values of similarity among 0.39-1.00 and 0.53-1.00, respectively. Differences should be attributed, partly, to the difficulty to determine the presence or absence of some of the bands of small intensity. The population from Misionera jungle showed smaller similarity with the pampeans that between each other. The results realized a considerable genetic uniformity among both putative entities that suggests the necessity to compare both additional populations in order to evaluate the consistency of these methods more objectively in their systematic characterization.